Genetic characterization of MDR genomic elements carrying two aac(6′)-aph(2″) genes in feline-derived clinical Enterococcus faecalis isolate - Li, Xue-Song; Qi, Yu; Li, Peng-hui; Xue, Jun-ze; Li, Xuan-yu; Muhammad, Inam; Li, Ya-zhuo; Zhu, Dao-mi; Ma, Ying; Kong, Ling-Cong; Ma, Hong-Xia (Frontiers in Microbiology, 2023)
Multidrug-resistant Enterococcus faecalis (E. faecalis) often cause intestinal infections in cats. The aim of this study was to investigate a multidrug resistant E. faecalis isolate for plasmidic and chromosomal antimicrobial resistance and their genetic environment. E. faecalis strain ESC1 was obtained from the feces of a cat. Antimicrobial susceptibility testing was carried out using the broth microdilution method. Conjugation experiments were performed using E. coli and S. aureus as receptors. Complete sequences of chromosomal DNA and plasmids were generated by whole genome sequencing (WGS) and bioinformatics analysis for the presence of drug resistance genes and mobile elements. Multidrug-resistant E. faecalis ESC1 contained a chromosome and three plasmids. The amino acid at position 80 of the parC gene on the chromosome was mutated from serine to isoleucine, and hence the amino acid mutation at this site led to the resistance of ESC1 strain to fluoroquinolones.Eleven antibiotic resistance genes were located on two plasmids. We identified a novel composite 删除的内容: College of Animal Medicine, 46